Crystallographic insights into lipid-membrane protein interactions in microbial rhodopsins - Bukhdruker, S.; Melnikov, I.; Baeken, C.; Balandin, T.; Gordeliy, V. (Frontiers in Molecular Biosciences, 2024)
The primary goal of our work is to provide structural insights into the influence of the hydrophobic lipid environment on the membrane proteins (MPs) structure and function. Our work will not cover the well-studied hydrophobic mismatch between the lipid bilayer and MPs. Instead, we will focus on the less-studied direct molecular interactions of lipids with the hydrophobic surfaces of MPs. To visualize the first layer of amphiphiles surrounding MPs and analyze their interaction with the proteins, we use the available highest-quality crystallographic structures of microbial rhodopsins. The results of the structure-based analysis allowed us to formulate the hypothetical concept of the role of the nearest layer of the lipids as an integral part of the MPs that are important for their structure and function. We then discuss how the lipid-MPs interaction is influenced by exogenous hydrophobic molecules, noble gases, which can compete with lipids for the surface of MPs and can be used in the systematic approach to verify the proposed concept experimentally. Finally, we raise the problems of currently available structural data that should be overcome to obtain a more profound picture of the lipid-MP interactions.